A multi-item Physician Global Assessment scale to assess psoriasis disease severity: validation based on four phase III tofacitinib studies - Callis Duffin, Kristina (BMC Dermatol, 2019)
BACKGROUND: Several different Physician Global Assessment (PGA) versions have been used in clinical studies as a co-primary end point to evaluate psoriasis severity. Tofacitinib is an oral Janus kinase inhibitor. We performed an analysis of the PGA using data from studies of tofacitinib in moderate to severe chronic plaque psoriasis. METHODS: Data from 3641 patients with moderate to severe chronic plaque psoriasis, enrolled in one of four phase III tofacitinib studies (OPT Pivotal 1 and 2, OPT Compare and OPT Retreatment), were used to evaluate a three-item PGA scale. RESULTS: Confirmatory Factor Analyses showed that equal weighting of the three items (erythema, induration and scaling) was appropriate. The PGA demonstrated acceptable test–retest reliability (Intraclass Correlation Coefficient, 0.7) and internal consistency (Cronbach’s Coefficient Alpha ≥ 0.9 at primary time points). The Clinically Important Difference was estimated as 0.55 (95% confidence interval: 0.546–0.563). Known-group validity was shown by demonstrating that PGA scores could discriminate between different degrees of disease severity. The PGA was significantly correlated with other clinical end points in the studies (Psoriasis Area and Severity Index, r = 0.75–0.79; Dermatology Life Quality Index, r = 0.44–0.57; Patient Global Assessment, r = 0.66–0.72). CONCLUSIONS: Consistent with previous findings from a phase II study, these results indicate that this PGA is a valid, reliable instrument for evaluating disease severity in clinical studies of psoriasis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12895-019-0088-2) contains supplementary material, which is available to authorized users.